Bacterial cyanide generation in the presence of metal ions (Na+, Mg2+, Fe2+, Pb2+) and gold bioleaching from waste PCBs - Tran, C.; Lee, J.; Pandey, B.; Jeong, J.; Yoo, Kyoungkeun; Huynh, T. (Journal of Chemical Engineering of Japan, 2011)
As an alternative using cyanide chemicals for gold extraction, the application of a cyanogenic bacterium viz. Chromobacterium violaceum (C. violaceum) in YP medium has been investigated. The catalytic roles of metal ions such as Na+, Mg2+, Fe2+, and Pb2+, as well as the effect of Na2HPO4 nutrient addition on the cyanide generation efficiency of the bacterium in this medium have been elucidated. While MgSO4 and FeSO4 added to the medium were equally effective for cyanide generation, improved efficiency was obtained in the presence of Na2HPO4 and Pb(NO3)2. In order to examine the effectiveness of C. violaceum cultured in YP medium for the generation of cyanide ions, the dissolution of gold and copper from waste mobile phone printed circuit boards (PCBs), a good source of gold and copper in alkaline conditions, was tested at 30°C, for various pH values and metal ion contents. Gold leaching was found to be 11% in 8 d at pH 11.0 in presence of 4.0 × 10−3 mol/L MgSO4, whereas; copper recovery was high (11.4%) at pH 10.0. Addition of 1.0 × 10−2 mol/L Na2HPO4 and 3.0 × 10−6 mol/L Pb(NO3)2 to the YP medium increased copper leaching to 30.3% and 38.1%, respectively, at pH 10.0 in 8 d. However, this effect was not observed for gold leaching.